2010
DOI: 10.1007/s12633-009-9029-8
|View full text |Cite
|
Sign up to set email alerts
|

UV-Visible and IR Spectroscopic Studies of Gamma Irradiated Transition Metal Doped Lead Silicate Glasses

Abstract: Lead silicate (LS) glasses of the basic composition PbO 75%, SiO 2 25% together with samples containing (∼0.1%) of transition 3d metal oxides (Ti→Cu) were prepared. UV/VIS optical analysis for as prepared and after successive gamma irradiated samples were used to shed more light on the structural modifications that occur due to different dopants and different irradiation doses. The UVVis. spectral analysis for undoped glass shows induced absorption bands at 205-400 nm which are assumed to be correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Indeed, if ionizing radiation strikes glasses, physical properties may alter remarkably. Among the possible changes, color centers have great significance [19,25,26]. However, G T is the sole sample without considerable change in appearance.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Indeed, if ionizing radiation strikes glasses, physical properties may alter remarkably. Among the possible changes, color centers have great significance [19,25,26]. However, G T is the sole sample without considerable change in appearance.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…A recent development in this research area concerning the spectroscopic studies of collective 3d-TM ions (from Ti to Cu) in various host glasses, as investigated by Abdelghany and co-workers, has indicated that that barium borate, and lead silicate glasses favor the presence of TM ions in their high valence states or tetrahedral coordination while the high P 2 O 5 content in the host glasses promotes low oxidation states or octahedral coordination [11][12][13][14][15].…”
Section: D-transition Metal (Tm) Ion-doped Glasses Exhibit Interestimentioning
confidence: 99%
“…Studies of radiation effects in glasses have been expanded recently due to their wide applications in optics on board space craft, in image guides for reactor inspection, in optical fiber wave guide and in immobilization of high level radioactive wastes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, exposure of high-energy ionizing radiation (such as crays, UV light, X-rays) on materials including glasses produces various interesting changes in their properties, which include chemical, electrical, magnetic, mechanical as well as optical properties [11,12].…”
Section: Introductionmentioning
confidence: 99%